Orenburg State University in the Conditions of Transformation - S. A. Miroshnikov (Высшее образование в России)
The article presents the key points of the development strategy of Orenburg State University with a focus on the criteria of the Strategic Academic Leadership Program “Priority 2030”. Transformations of popular models of university development in the historical logic are considered, actual models in an international and regional scale are highlighted. The article makes the case for transition from the adaptation strategy of the university development to the strategy of a driver of positive changes in the Orenburg Region. The resources of the OSU leadership strategy and tactical solutions for the implementation of the OSU mission – “Development of territory and human capital” in various types and scales of influence are determined.